Analysis of Assessment Instrument For Tahfiz Al-Qur’an at East Jakarta Elementary School - Ernawati, Ernawari; Wahjusaputri, Sintha; Giyanti, Giyanti; Setiadi, Hari (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of this study is to examine the tahfiz Al-Qur'an instrument developed by teachers at an elementary school in East Jakarta. The descriptive qualitative methodology was adopted in this research. This study's subject was teachers that teach tahfiz Al-Qur’an at elementary schools in East Jakarta, and the object was twelve instruments created by Tahfiz teachers in East Jakarta. The data gathering method is carried out by assessing the instruments developed by teachers. The instruments were analyzed by two experts and discussed in Forum Group Discussion (FGD) and engaged practitioners, there were tahfiz teachers in East Jakarta. Beside that the, the data collection is carried out through interviews dan document study. The interview guide is used to reinforce the data related to the tahfiz teacher's knowledge of the concept of assessment. The results showed that the assessment instrument made by tahfiz teachers at the elementary school level in East Jakarta still needs to be revised to meet the assessment principles. These instruments also need to be developed to produce systematic scoring criteria and guidelines. The conformity level on material aspect on average score 2,61; construct aspect on average score 1,42; usage language aspect on average score 2,10, and average total conformity on score 2,04.